2012
DOI: 10.1074/jbc.c111.318501
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Yeast Kinetochore Ndc10 DNA-binding Domain Reveals Unexpected Evolutionary Relationship to Tyrosine Recombinases

Abstract: Background: Ndc10 is a DNA-binding protein in yeast that is responsible for centromere formation. Results: The structure of the protein unexpectedly shows that it contains a type IB topoisomerase/-integrase fold. Conclusion:The structure demonstrates how the IB/Int fold has been adapted to a new cellular role. Significance: The structure is the first example of the IB/Int fold being used in a non-catalytic protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…Previous studies have suggested that Ndc10 and Cep3 constitute the DNA-binding activities of the complex. Both Ndc10 and Cep3 are capable of directly binding DNA (Espelin et al, 1997;Purvis & Singleton, 2008;Cho & Harrison, 2011;Perriches & Singleton, 2012); in the case of Cep3, sequence specificity for the CDEIII element is provided by zinc-containing Gal4-type DNA-binding domains (Strunnikov et al, 1995;Espelin et al, 1997). The function of Ctf13 and Skp1 has remained obscure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have suggested that Ndc10 and Cep3 constitute the DNA-binding activities of the complex. Both Ndc10 and Cep3 are capable of directly binding DNA (Espelin et al, 1997;Purvis & Singleton, 2008;Cho & Harrison, 2011;Perriches & Singleton, 2012); in the case of Cep3, sequence specificity for the CDEIII element is provided by zinc-containing Gal4-type DNA-binding domains (Strunnikov et al, 1995;Espelin et al, 1997). The function of Ctf13 and Skp1 has remained obscure.…”
Section: Introductionmentioning
confidence: 99%
“…Exactly how these pathways contribute to the assembly of mature, centromere-binding proficient CBF3 is still not entirely clear. Crystal structures have been determined of the truncated Cep3 and Ndc10 proteins (Bellizzi et al, 2007;Purvis & Singleton, 2008;Cho & Harrison, 2011;Perriches & Singleton, 2012) as well as full-length Skp1 (Schulman et al, 2000;Orlicky et al, 2003). However, we are missing structural data for Ctf13 and crucially, the intact CBF3 complex.…”
Section: Introductionmentioning
confidence: 99%
“…The complex contains four essential proteins that are most commonly referred to as Ndc10 (Cbf3a/ Cbf2/Ctf14/p110) (Doheny et al 1993;Goh and Kilmartin 1993;Jiang et al 1993), Cep3 (Cbf3b/p64) (Lechner 1994;Strunnikov et al 1995), Ctf13 (Cbf3c/p58) (Doheny et al 1993), and Skp1 (Cbf3/p19) (Connelly and Hieter 1996;Stemmann and Lechner 1996). Cep3 has a Zinc-cluster motif found in transcription factors (Dhawale and Lane 1993;Strunnikov et al 1995;Schjerling and Holmberg 1996) and Ndc10 was recently shown to have structural similarity to tyrosine DNA recombinases (Cho and Harrison 2012;Perriches and Singleton 2012), although it does not exhibit catalytic activity or DNA base sequence specificity. Consistent with this, Ndc10 (in the absence of CBF3) can also bind to the CDEII element in vitro as well as other genomic regions that are AT rich, although these activities are not known to be relevant to CBF3 assembly in vivo (Espelin et al 2003).…”
Section: Inner Centromere Binding Proteinsmentioning
confidence: 99%
“…Ndc10 is distantly related to the tyrosine DNA recombinases, such as CRE (Cho and Harrison 2012; Perriches and Singleton 2012). Ndc10 may be central to the controversy surrounding the Cse4 nucleosome, as well as the structure of the inner centromere.…”
Section: Characteristics Of Centromere Chromatin—primary Folding Of Amentioning
confidence: 99%